Phasic and Tonic mGlu7 Receptor Activity Modulates the Thalamocortical Network - Tassin, Valériane; Girard, Benoît; Chotte, Apolline; Fontanaud, Pierre; Rigault, Delphine; Kalinichev, Mikhail; Perroy, Julie; Acher, Francine; Fagni, Laurent; Bertaso, Federica (Frontiers in Neural Circuits, 2016)
Mutation of the metabotropic glutamate receptor type 7 (mGlu7) induces absence-like epileptic seizures, but its precise role in the somatosensory thalamocortical network remains unknown. By combining electrophysiological recordings, optogenetics and pharmacology we dissected the contribution of the mGlu7 receptor at mouse thalamic synapses. We found that mGlu7 is functionally expressed at both glutamatergic and GABAergic synapses, where it can inhibit neurotransmission and regulate short-term plasticity. These effects depend on the PDZ-ligand of the receptor, as they are lost in mutant mice. Interestingly, the very low affinity of mGlu7 receptors for glutamate raises the question of how it can be activated, namely at GABAergic synapses and in basal conditions. Inactivation of the receptor activity with the mGlu7 negative allosteric modulator (NAM), ADX71743, enhances thalamic synaptic transmission. In vivo administration of the NAM induces a lethargic state with spindle and/or spike-and-wave discharges accompanied by a behavioral arrest typical of absence epileptic seizures. This provides evidence for mGlu7 receptor-mediated tonic modulation of a physiological function in vivo preventing synchronous and potentially pathological oscillations.